A larval transcriptome of the limnephilid caddisfly Micropterna lateralis (Stephens, 1837) (Trichoptera: Limnephilidae). Issue 3 (2nd July 2016) - Hoppeler, Felicitas; Rotter, Björn; Krezdorn, Nicolas; Pauls, Steffen U.
ABSTRACT: The aquatic caddisfly Micropterna lateralis (Stephens, 1837) is adapted to intermittent streams. Normally, the species persists drought conditions by means of an adult diapause, yet active larvae, pupation and emergence have been observed on dry stream beds. The species, thus, presents a good example to study the molecular basis of local adaptation to different hydrological conditions and freshwater habitat types, but genomic resources are lacking to date. We isolated total RNA and applied Illumina RNA-Seq to a pool of eight larval specimens sampled under different hydrological conditions during a drought experiment simulating stream intermittency. Sequencing resulted in 108′011′306 high-quality reads that were de novo assembled into 17, 759 contigs, of which 16, 848 were matched to protein sequences from Insects. The transcriptome of M. lateralis is providing a valuable resource for future investigations of molecular mechanisms in drought adaptation in aquatic insects and the secondary invasion of freshwater habitats by insects in general.